ICT Integration in the Islamic Religious Education Learning Process - Dahliana, Dina; Yelni, Setria; Yumna, Yumna; Azima, Nana Fauzana (International Journal of Islamic Teaching and Learning, 2024)
One of the factors that causes low student scores includes a lack of encouragement for students to develop thinking skills. Increasing students' understanding can be done by integrating ICT using the Role Playing method, because students can demonstrate learning material directly by playing roles with the help of ICT. Therefore, this research aims to explain how to improve student learning outcomes by using the Role Playing method. This research uses quantitative methods with a classroom action research approach. Data sources were taken using questionnaires and oral tests on 22 people consisting of 12 male students and 10 female students. Overall, the research results show that the use of the role playing method shows quite significant improvements, especially in the cognitive domain. Therefore, integrating ICT using role playing is an alternative in improving Islamic Religious Education learning outcomes.